1998
DOI: 10.1111/j.1745-4514.1998.tb00247.x
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for Particle Size Effect on Rates of Enzymatic Saccharification of Microcrystalline Cellulose

Abstract: Commercially available microcrystalline cellulose (MCC) preparations are widely used as substrates for the characterization of cellulolytic enzymes. The intent of this paper is to demonstrate the importance of considering particle size when using these substrates and to provide a rationale for particle‐size related phenomena. Rates of saccharification of MCC substrates having average particle sizes of 20, 50 and 100 μm were compared under typical Trichoderma reesei cellulase‐based saccharification conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…Furthermore, the high level of added microbial phytase may allow a greater degradation of phytate in SBM regardless of particle size. Results of the current study support the statement of Silva et al (2012), Sangseethong et al (1998) and Mansfield et al (1999) that particle size reduction enhanced the contact between enzyme and substrate (speeding up the initial rates) and exposed the inaccessible zones in coarse particles (increasing the final hydrolysis yields). The surface area of maize increased by four times when the APS decreased from 2010 to 525 µm (Summers, 2001).…”
Section: Phytate P Degradationsupporting
confidence: 87%
“…Furthermore, the high level of added microbial phytase may allow a greater degradation of phytate in SBM regardless of particle size. Results of the current study support the statement of Silva et al (2012), Sangseethong et al (1998) and Mansfield et al (1999) that particle size reduction enhanced the contact between enzyme and substrate (speeding up the initial rates) and exposed the inaccessible zones in coarse particles (increasing the final hydrolysis yields). The surface area of maize increased by four times when the APS decreased from 2010 to 525 µm (Summers, 2001).…”
Section: Phytate P Degradationsupporting
confidence: 87%
“…Numerous studies have shown improvement in enzymatic action attributable to mechanical comminution of substrate due to changes in particle size and crystallinity, and the increase in surface area [12][13][14][15]. However, limited information is available on the effect of mechanical grinding/comminution on composition of feedstock fractions that might favor enhanced enzymatic action for one fraction over others.…”
Section: Introductionmentioning
confidence: 96%
“…It is important to have reproducibility in the milling process to minimize variability in particle size distribution. Mass transfer limitations within the agglomerate particles that make up these substrates are responsible for variation in saccharification rates as a function of particle size (Sangseethong et al, 1998). Several models for cellulose and lignocellulose hydrolysis have been developed over the years that incorporate various parameters into the kinetic model.…”
Section: Particle Size Distributionmentioning
confidence: 99%